Epistemic Oscillation: Living With Ocean Risks - Irina Rafliana (Ocean and Society)
The year 2024 marks two decades since the Indian Ocean tsunami, known as the Boxing Day catastrophe, which far surpassed other devastating geological events of the 21st‐century on humankind. Paradoxically, the epitome of tsunamis carries regenerative agency. It moves science and technologies across territories, proliferates knowledge production, and boosts innovations of warning systems as a critical part of ocean risk governance. In many cases, humans gradually distanced themselves from memories of past events due to the “high risk and low return period” of events. Through diverse risk perceptions, cultures, and beliefs, coupled with rapid human mobilities, the once proliferated knowledge could also be unlearned and forgotten. When knowledge on tsunamis is scarce or about to become extinct, no earthly process greater than tsunamis could bring back and sustain such knowledge. Like tsunami waves, this article argues that knowledge also refracts and oscillates. This article proposes epistemic oscillation as a conceptual lens as one of the ways to understand complex human and non‐human entanglements, highlighting humans’ dependent relations to geological dynamics, using the cases of the Palu 2018 tsunami as a testbed. By doing so, the article also argues that such lenses are useful in tracing the importance of understanding ambiguities in tsunami risk governance. By deploying an affective turn to ocean materialities and micropolitics as research methods, this article proposes alternative ways to unfold the multiplicities of social and geological realities and epistemic mobilities in the hyper‐complex challenges of knowledge integration and ocean risk governance.